Management of Patients With Glomerulonephritis During the COVID-19 Pandemic: Recommendations From the Canadian Society of Nephrology COVID-19 Rapid Response Team. (November 2020) - Moran, Sarah M.; Barbour, Sean; Dipchand, Christine; Garland, Jocelyn S.; Hladunewich, Michelle; Jauhal, Arenn; Kappel, Joanne E.; Levin, Adeera; Pandeya, Sanjay; Reich, Heather N.; Thanabalasingam, Susan; Thomas, Dorothy; et al.
Purpose of program: This article will provide guidance on how to best manage patients with glomerulonephritis (GN) during the COVID-19 pandemic. Sources of information: We reviewed relevant published literature, program-specific documents, and guidance documents from international societies. An informal survey of Canadian nephrologists was conducted to identify practice patterns and expert opinions. We hosted a national webinar with invited input and feedback after webinar. Methods: The Canadian Society of Nephrology (CSN) Board of Directors invited physicians with expertise in GN to contribute. Specific COVID-19-related themes in GN were identified, and consensus-based recommendations were made by this group of nephrologists. The recommendations received further peer input and review by Canadian nephrologists via a CSN-sponsored webinar. This was attended by 150 kidney health care professionals. The final consensus recommendations also incorporated review by Editors of the Canadian Journal of Kidney Health and Disease . Key findings: We identified 9 areas of GN management that may be affected by the COVID-19 pandemic: (1) clinic visit scheduling, (2) clinic visit type, (3) provision of multidisciplinary care, (4) blood and urine testing, (5) home-based monitoring essentials, (6) immunosuppression, (7) other medications, (8) patient education and support, and (9) employment. Limitations: These recommendations are expert opinion, and are subject to the biases associated with this level of evidence. To expedite the publication of this work, a parallel review process was created that may not be as robust as standard arm's length peer review processes. Implications: These recommendations are intended to provide optimal care during the COVID-19 pandemic. Our recommendations may change based on the evolving evidence.